A rare presentation of Sjogren\'s syndrome with ascites and liver fibrosis in a young woman: a Case report - Mohammad Reza Farzaneh Far; Maryam Miri; Farimah Naghibian; Forouzan Amerizadeh; Masoumeh Salari (مجله دانشگاه علوم پزشکی بیرجند)
Primary Sjogren's syndrome is a systemic autoimmune disease that encompasses a wide range of manifestations, including exocrine gland involvement and extra-glandular symptoms. This case report deals with the history of a 26-year-old woman presented with ascites and peripheral edema and without any medical history or recent drug use. Initial tests demonstrated leukopenia, anemia, and thrombocytopenia, as well as normal liver and kidney function.  Ascitic fluid analysis A indicated liver involvement, and imaging displayed significant fibrosis in the liver. Additional laboratory tests showed positive antinuclear antibodies (ANA), anti-Sjögren's syndrome-related antigen A (SS-A), and anti-Sjögren's syndrome-related antigen B (SS-B) antibodies. Moreover, a minor salivary gland biopsy confirmed the diagnosis of Sjogren's syndrome. The patient was treated with prednisolone, hydroxychloroquine, and mycophenolate mofetil, which led to the reduction of ascites and edema and the improvement of cytopenia. This report highlighted the importance of considering Sjogren's syndrome in patients with liver fibrosis and unexplained ascites.